2019
DOI: 10.1002/nau.24004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of LUTS on treatment‐related behaviors and quality of life: A population‐based study in Brazil

Abstract: AimsTo report on the impact of lower urinary tract symptoms (LUTS) on treatment‐related behaviors and quality of life in Brazilian adults greater than or equal to 40 years.MethodsData were from a computer‐assisted telephone survey conducted in Brazil between 1 September and 31 December 2015 (Brazil LUTS study). Participants were adults greater than or equal to 40 years with landlines living in major cities from five geographical regions in Brazil. Participants rated how often they experienced individual LUTS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The results are congruent with the research as the UDI-6 score was found to be predictive for urodynamic diagnoses, especially urinary incontinence and detrusor overactivity and obstruction, but not for the severity of incontinence [20]. Soler et al [21] demonstrated that in the presence of LUTS less than half the time or more, onequarter of respondents sought treatment but 6% fewer received treatment.…”
Section: Discussionsupporting
confidence: 78%
“…The results are congruent with the research as the UDI-6 score was found to be predictive for urodynamic diagnoses, especially urinary incontinence and detrusor overactivity and obstruction, but not for the severity of incontinence [20]. Soler et al [21] demonstrated that in the presence of LUTS less than half the time or more, onequarter of respondents sought treatment but 6% fewer received treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Collectively, these data suggest there is a substantial burden of OAB in Latin America, with some evidence to indicate its important impact on QoL and low rates of treatment-seeking behavior, especially among older people 15 . Moreover, a paper on the impact of LUTS on treatment-related behaviors and QoL showed that treatment seeking and treatment rates for LUTS are low 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, an Internet survey with participants from South Korea, Taiwan, and China showed that 26% of respondents with any LUTS reported visiting healthcare professionals because of their LUTS [ 4 ]. The Brazil LUTS, a telephone interview conducted in five major cities of Brazil, documented that up to 30.6% of respondents with LUTS sought treatment [ 18 ]. Our observation of treatment seeking by 29.6% of adults in Poland who reported LUTS is broadly comparable with the foregoing population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding findings have been reported in some previous studies [ 8 , 24 ]. Some experts account for this difference by noting that women usually start earlier than men with a routine of frequent healthcare visits [ 18 ].…”
Section: Discussionmentioning
confidence: 99%